NOVEL EVIDENCE THAT BETA-ADRENOCEPTORS OF THE MEDIAL SEPTAL AREA REGULATE BLOOD-PRESSURE AND ELECTROLYTE BALANCE - Saad, W. A.; Menani, José Vanderlei [UNESP]; Camargo, LAA; Antunesrodrigues, J. (Elsevier B.V., 1995)
We investigated the participation of the beta-adrenoceptors of the septal area (SA) in sodium and potassium excretion and urine flow. The alterations in arterial pressure and some renal functions were also investigated. The injection of 2.10(-9) to 16.10(-9)M of isoproterenol, through a cannula permanently implanted into the SA produced a significant dose-dependent decrease in urinary Na+ and K+ excretion and urinary flow. Pretreatment with 16.10(-9) M butoxamine antagonized the effect of 4.10(-9) M isoproterenol but pretreatment with 16.10(-9) M practolol did not abolish the effect of isoproterenol. The beta 2-agonist terbutaline and salbutamol (4.10(-9) M when injected intraseptally also caused a decrease in urine flow and in renal Na+ and K+ excretion. After injection of isoproterenol or salbutamol (4.10(-9) M) into the SA, the arterial pressure, glomerular, filtration rate (GFR) and filtered Nd were reduced while Na+ fractional reabsorption was increased. The results indicate that the beta 2-adrenoceptors of the SA play a role in the decrease of Na+, K+ and urine flow and this effect may be due to a drop in GFR and filtered Na+ and to the rise in tubular Na+ reabsorption.
Keywords: SEPTAL AREA; ELECTROLYTE BALANCE; BLOOD PRESSURE